Inside Cover: Behavior of Highly Diluted Electrolytes in Strong Electric Fields—Prevention of Alumina Deposition on Grading Electrodes in HVDC Transmission Modules by CO2‐induced pH‐Control (Chem. Eur. J. 38/2014). Issue 38 (15th September 2014) - Weber, Immo; Mallick, Bert; Schild, Matthias; Kareth, Sabine; Puchta, Ralph; van Eldik, Rudi
<x xml:space="preserve">Abstract</x> Alumina deposition on platinum grading electrodes in high voltage direct current (HVDC) transmission modules is an unsolved problem that has been around for more than three decades. In their Full Paper on page 12091 ff., R. van Eldik and I. Weber discuss this problem in detail and present pulse purging with pure CO2 gas as a technical solution to prevent the deposition of alumina.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>